Border walls. A legal approach in light of the human rights - Enrico Headrington, Alessandra (2019)
The objective of this article is to analyze the complex problem of border walls. Specifically, it introduces a legal lens to the issue in order to determine whether these border walls could affect the exercise of individual human rights. With this purpose in mind, the phenomenon of border walls is examined from historical and political perspectives, concluding that since the fall of the Berlin wall and the advent of globalization, these physical barriers stand as a significant contradiction to a world that is supposedly freer and more open. It also purports to examine the general social contexts and justifications that explain why states resort to building walls on their borders. The article then addresses the constant tension between two considerations: on the one hand, the appeal to state sovereignty, and on the other, the human rights of the particular people and communities on the border lines. It emphasizes that state sovereignty must evolve in conjunction with the humanization of international law. Finally, the article discusses the two required elements to establish state responsibility in the context of border walls. For example, the commission of a wrongful act, such as the violation of the right to life or the right to physical integrity, constitutes a breach of an international obligation, which satisfies the first requirement to establish state responsibility. To fulfill the second requirement, the wrongful act must be attributed to the state, which is possible if the order for construction qualifies as a governmental act. That being said, a finding of state responsibility in this context per se is inevitably a case-specific analysis.